The History of the Introduction of the Concept of Depression Into China - Bai, Jike; Li, Jun; Zhang, Daqing (Frontiers in Psychiatry, 2022)
This is a thematic historical study on the historical construction of the concept of depression in early modern China. Using an external historical research method, through the analysis of newspaper stories, drug advertisements, and medical texts (textbooks and reference books), it presents the socio-cultural context of depression in the late Qing Dynasty and early Republican period and depicts the germination and evolution of the depression from a hazy and ambiguous concept in the late Qing Dynasty to a clear and complete disease entity of Western medicine, at least in the Chinese pharmaceutical market in the 1920s. This paper examines the three internal logical clues in the localization of depression in China: First, the transformation of the disease from a symptom (the symptom of a disease) to a disease (an independent disease entity); Second, the pathological mechanism of depression was first made from the perspective of Traditional Chinese Medicine— “caused by stagnation of liver qi” , which was joined later by the pathological mechanism of Western medicine—"caused by brain dysfunction"; Third, the introduction of the knowledge of "depression" presents a pattern of "cross-fertilization" between the West and the East. This study also examines the cultural imagery of depression during its early introduction to China and finds the three stereotypes of the manifestation of depression among the then Chinese public: a feminized disease, a disease that afflicted the intellectual youth who were worried about the country, and the association between the disease and the morbid and distorted state of life of the upper-class literary youth.